2018
DOI: 10.3390/ijerph15061082
|View full text |Cite
|
Sign up to set email alerts
|

Location of Femoral Fractures in Patients with Different Weight Classes in Fall and Motorcycle Accidents: A Retrospective Cross-Sectional Analysis

Abstract: Background: This study aimed to determine the incidence of femoral fracture location in trauma patients with different weight classes in fall and motorcycle accidents. Methods: A total of 2647 hospitalized adult patients with 2760 femoral fractures from 1 January 2009 to 31 December 2014 were included in this study. Femoral fracture sites were categorized based on their location: proximal femur (type A, trochanteric; type B, neck; and type C, head), femoral shaft, and distal femur. The patients were further cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 27 publications
0
21
0
2
Order By: Relevance
“…In obese patients, increased soft tissue padding around the hip attenuates the greater impact forces that result from falls and reduces the force transmitted to the bone [15, 16]. In contrast, obese patients had a higher odds risk for shaft and distal femoral fractures in fall accidents [4]. In this type of scenario, the body weight associated with obesity would increase the impact force but provide less protection in the shaft and distal region of the femur.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In obese patients, increased soft tissue padding around the hip attenuates the greater impact forces that result from falls and reduces the force transmitted to the bone [15, 16]. In contrast, obese patients had a higher odds risk for shaft and distal femoral fractures in fall accidents [4]. In this type of scenario, the body weight associated with obesity would increase the impact force but provide less protection in the shaft and distal region of the femur.…”
Section: Discussionmentioning
confidence: 99%
“…The factors influencing femoral fracture site are interrelated and are not independent. For example, increasing age is associated with osteoporotic bone changes, which are believed to increase the rate of femoral fracture; falls occur more frequently in the elderly [3, 4] but traffic-related fractures caused by motorcycle or bicycle accidents occur more often in younger adults and the rate of its occurrence differs between genders [4, 5]. In a fall accident, the force directly impacts the posterolateral aspect of the greater trochanter, but the impact point is not limited to only this site in a non-fall accident.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elderly individuals are at the greatest risk of a fall accidents [1,2] and their consequences, such as fractures, immobility, and sometimes even death [3][4][5][6][7]. In addition to pain, a femoral fracture results in a curtailment of physical activity, increased dependence, and rapid worsening of the health status.…”
Section: Introductionmentioning
confidence: 99%
“…There is an evidence that femoral shaft fractures have frequent assosciation with skeletal injuries (46.4%) and one-fourth of cases had occult assocaited injuries [8]. Notably, many studies have reported the presence of assosciated injuries such as hemothorax, bowel and head injuries concomitant with femur shaft fracture which dictates the severity of injury [8][9][10]. Of note, there are certain factors such as age, gender, mechanism of injury and magnitude of traumatic impact which might in uence the site of femoral fracture [11,12].…”
Section: Introductionmentioning
confidence: 99%